Crecimiento del pez palo, Percophis brasiliensis Quoy y Gaimard, 1824, del Atlántico Sur (Perciformes, Trachinoidei) - San Roman, Nemesio Amaro (1974)
Nine hundred specimens of Percophis brasiliensis, a fish know as “pez palo” in the South Atlantic (Mar del Plata) are studied as a part of more extensive biological investigations. The relationships between length and age, length and weight, weight and age and condition factor are given; the correlation (r) is high in all cases. There are a progressive differentiation in the growth between males and females. The maximal age in males is 6 years, with lengths between 500 and 590 mm ; in females the maximal age is 7 years with lengths between 550 and 690 mm.